KAJIAN HUKUM TERHADAP PENERAPAN SISTEM E-TILANG DALAM PENANGANAN PELANGGARAN PIDANA LALU LINTAS DI KOTA DENPASAR : A Legal Analysis of the E-Ticketing System Implementation for Traffic Infraction Management in Denpasar City - Yadnya, Putu Andhika Kusuma; Suradigama, I Wayan; Nurcana, I Dewa Nyoman Gde; Pramana, I Gusti Agus Yuda Trisna (Ganec Swara, 2025)
The rapid growth of vehicles has made traffic law enforcement a critical issue in urban areas. This normative legal research examines the implementation of the e-ticketing system in handling traffic violations in Denpasar City. The study finds that the implementation of e-tilang has a strong and multi-level legal foundation, primarily based on Law Number 22 of 2009 concerning Traffic and Road Transportation, supported by other regulations such as the ITE Law and the Personal Data Protection Law. However, the research also identifies significant legal consequences, including a shift towards objective liability for vehicle owners and challenges related to the protection of constitutional rights, such as the right to be heard and data privacy. While the system aligns with the principles of good governance, particularly in transparency, accountability, and efficiency, its full success depends on massive socialization, clear complaint mechanisms, and affirmative policies for the technologically vulnerable. The study concludes that e-tilang is a legitimate instrument for law enforcement in the digital era, provided it is balanced with a strong commitment to data protection and all principles of good governance.